Pendidikan Nilai dalam Era Pluralitas - ruslan ibrahim (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Values education is activity which help students in order that they have instruction which determine all of their actions. Values education is considered urgent in education activity. It is purposed to build social solidarity, especially in religion and cultural plurality era. The reality of social, religion, and cultural conflict, showed education functions as transfer of moral values still optimal yet. Therefore, values education include moral training must be aplicated to help students be up against social problems in their life.Â